Towards a Domain Independent Platform for Data Cleaning - Arasu, Arvind; Chaudhuri, Surajit; Chen, Zhimin; Ganjam, Kris; Kaushik, Raghav; Narasayya, Vivek (Data Engineering Bulletin, 2011)
We present a domain independent platform for data cleaning developed as part of the Data Cleaning project at Microsoft Research. Our platform consists of a set of core primitives and design tools that allow a programmer to develop sophisticated data cleaning solutions with minimal programming effort. Our primitives are designed to allow rich domain and application specific customizations and can efficiently handle large inputs. Our data cleaning technology has had significant impact on Microsoft products and services and has been successfully used in several real-world data cleaning applications.